Much ado about nothing? State-controlled entities and the change in German investment law - Thomas Jost (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
Despite a tightening of German foreign investment law in 2009 in reaction to the growing importance of state controlled entities and national security concerns, Germany has remained open for FDI. So far German authorities have handled the new law carefully. But, was the change necessary?
Keywords: 330